Assessment of Factories on Adherence to COVID-19 Standard Operating Procedures: A Case Study of Wakiso, Mukono, Buikwe, and Jinja Districts, Uganda - Joseph M. Kungu; Edity Namyalo; Angella Musewa; Sarah Nitumusiima; Phiona Keije; Catherine Nakakooza; Osborn Oyirwoth (Journal of Tropical Medicine)
Background. Coronavirus disease (COVID-19) is an infectious disease caused by the SARS-CoV-2 virus. Uganda confirmed the first case of COVID-19 on 21st March, 2020, which led to the first total lockdown in the country. During the lockdown, some factories remained operational; hence, there is a need for a study aimed at assessing the level of adherence to COVID-19 standard operating procedures (SOPs) in factories as a mitigator for the pandemic. Methods. A cross-sectional study to assess compliance of factories to COVID-19 SOPs was conducted in Wakiso, Mukono, Buikwe, and Jinja districts during the month of September, 2021. This involved visitation of factories and collection of data using the KoboCollect tool by interviewing general managers as well as human resource managers of the factories. A total of 39 factories were included in the study and were categorized into four major groups; food and beverages (15), plastics (5), construction (8), and others (11). Data analysis was done using STATA version 14.2. Results. Overall adherence to COVID-19 SOPs by the factories was 64.1% (95% CI = 49.1–79.1). Communication and training of employees (79.5%; 95% CI = 66.8–92.2), wearing personal protective equipment (PPE), and respiratory protection (79.5%; 95% CI = 66.8–92.2) as well as enhanced cleaning and disinfection of surfaces (74.4%; 95% CI = 60.6–88.1) were the most implemented SOPs in the factories. Implementation of the SOPs was the highest in Mukono district (88.9%; 95% CI = 68.4–100) and the least in Wakiso district (40.0%; 95% CI = 9.6–70.4). The COVID-19 SOPs were followed mostly in construction material factories (87.5%; 95% CI = 64.6–100) and least in food and beverage factories (40%; 95% CI = 15.2–64.8). There was no significant difference in the adherence of COVID-19 SOPs among the districts (X2 = 5.02 and P=0.17) and factories (X2 = 7.04 and P=0.07). Although good overall adherence to SOPs noted was not dependent on location and type of factory, adherence to some SOPs such as exposure control plan, presence of signages on COVID-19, maintenance of social distance, and implementation of a health control plan varied with location of the district. Likewise, exposure control plan, signages on COVID-19, and maintenance of social distance varied significantly with the type of factory. Conclusion. This study revealed moderately good overall adherence to COVID-19 SOPs by factories, with variations in the level of implementation of individual SOPs being observed.